Depression, Self-Esteem, Coping Strategies, Social Support, and Hopelessness as Predictors of Psychological Distress among Unemployed Graduates in Lagos, Nigeria - Akinyemi, Olukemi Yetunde (NIU Journal of Social Sciences, 2025)
Unemployment remains a major socio-economic challenge with profound implications for the psychological well-being of young graduates. This study investigated the predictive roles of depression, self-esteem, coping strategies, social support, and hopelessness in psychological distress among unemployed graduates in Nigeria. A correlational research design was adopted, and data were collected from 126 unemployed graduates using standardised psychological instruments. Multiple regression analysis revealed that the predictors jointly accounted for 55% of the variance in psychological distress (R = .74, R² = .55, Adjusted R² = .52, F(5,120) = 18.46, p < .01). Depression and hopelessness significantly increased psychological distress, while self-esteem, coping strategies, and social support functioned as protective factors. These findings underscore the complex interplay of individual and social variables in shaping unemployed youths’ mental health. The study concludes that interventions addressing depression and hopelessness, alongside programmes promoting resilience, social connectedness, and self-worth, are crucial for alleviating distress among unemployed graduates. It recommends multi-level approaches involving counselling, institutional support, and policy-driven initiatives to enhance psychological well-being and reduce the adverse mental health outcomes associated with graduate unemployment. Keywords: unemployment, psychological distress, depression, self-esteem, coping strategies, social support, hopelessness